Combined Diagnosis of Systemic Lupus Erythematosus and Tuberculosis in an Irish Adolescent Female - Kene Ebuka Maduemem; Comfort O. Adedokun; Adela Vatca (Case Reports in Pediatrics)
Systemic lupus erythematosus (SLE) is an autoimmune disease of unknown aetiology, which can affect any organ system. Tuberculosis (TB) is a common infection in SLE because of immune dysregulation associated with the latter. We report a case of an adolescent female who presented with a year’s history of polyarticular arthralgia and fever. Physical examination revealed a large left effusion that needed drainage. Investigations revealed a combined diagnosis of SLE and TB. Management comprised quadruple anti-TB therapy and SLE treatment. She made a steady recovery and has maintained a stable state from the lupus perspective.